Combinatorial Analysis of AT-Rich Interaction Domain 1A and CD47 in Gastric Cancer Patients Reveals Markers of Prognosis - Zhao, Qianfu; Cai, Qu; Yu, Shanhe; Ji, Jun; Zhu, Zhenggang; Yan, Chao; Zhang, Jun (Frontiers in Cell and Developmental Biology, 2021)
Background: The AT-rich interaction domain 1A (ARID1A) is thought to be a tumor suppressive gene, and most of its mutations result in loss of expression of ARID1A protein. Combined with SIRPα on the surface of macrophages, CD47 on the surface of cancer cells can send an antiphagocytic “Don’t eat me” signal to the immune system that helps to avoid immune surveillance. However, the relationship between ARID1A and CD47 expression and their prognostic value in gastric cancer (GC) are still unknown. Methods: In this study, we evaluated ARID1A and CD47 expression in 154 GC patients’ tissues using tissue microarray. Expressions of ARID1A and CD47 in GC cell lines were determined by western blot and quantitative reverse transcriptase–polymerase chain reaction (qRT-PCR) techniques, and cell membranous CD47 expression was quantified by flow cytometry. In addition, chromatin immunoprecipitation (ChIP)–qPCR was used to determine the aspects of regulation of CD47 by ARID1A. The proportions of tumor-infiltrating immune cells were estimated on The Cancer Genome Atlas (TCGA) data set by using quanTIseq and EPIC algorithms. The infiltration of M1-polarized macrophages, M2-polarized macrophages, and regulatory T cells (Tregs) in GC tissues was determined by multispectral immunofluorescence. Results: A significant correlation was found between loss of ARID1A and high expression of CD47 at protein level in GC. By integrating 375 bulk RNA sequencing samples from TCGA data set, we found that mutated ARID1A correlated with high CD47 expression. In GC cell lines, knockdown of ARID1A significantly increased CD47 expression both at protein and mRNA levels as measured by western blot, qRT-PCR, and flow cytometry. Moreover, ChIP-qPCR revealed that CD47 was a direct downstream target gene of ARID1A in GC. Utilizing univariate and multivariate survival analyses, we found that patients with ARID1AlossCD47high expression had a worse prognosis. Estimation of infiltrating immune cells on TCGA data set showed that a higher infiltration proportion of M2 macrophages and Tregs was found in ARID1AmutatedCD47high expression subgroup. Furthermore, application of multispectral immunofluorescence revealed a higher infiltration proportion of M2 macrophages and Tregs in ARID1AlossCD47high GC tissues. Conclusion: Loss of ARID1A is strongly correlated with high CD47 expression in GC, and combination of ARID1A and CD47 is a promising prognosis factor in GC.